Defects in mTORC1 Network and mTORC1-STAT3 Pathway Crosstalk Contributes to Non-inflammatory Hepatocellular Carcinoma - Li, Ting; Zhang, Guohong; Wang, Linlin; Li, Susu; Xu, Xiaoping; Gao, Yi (Frontiers in Cell and Developmental Biology, 2020)
Background & Aims: Mammalian target of rapamycin complex 1 (mTORC1) is frequently hyperactivated in hepatocellular carcinoma (HCC). Cases of HCC without inflammation and cirrhosis are not rarely seen in clinics. However, the molecular basis of noninflammatory HCC remains unclear. Methods: Spontaneous noninflammatory HCC in mice was triggered by constitutive elevation of mTORC1 by liver-specific Tsc1 knockout (LTsc1KO). A multi-omics approach was utilized on tumor tissues to better understand the molecular basis for the development of HCC in the LTsc1KO model. Results: We showed that LTsc1KO in mice triggered spontaneous noninflammatory HCC, with molecular characteristics similar to those of diethylnitrosamine-mediated noncirrhotic HCC. Mitochondrial and autophagy defects, as well as hepatic metabolic disorder were manifested in HCC development by LTsc1KO. mTORC1 activation on its own regulated an oncogenic network (DNA-damage-inducible transcript 4, nuclear protein 1 and fibroblast growth factor 21), and mTORC1–signal transducer and activator of transcription pathway crosstalk that altered specific metabolic pathways contributed to the development of noninflammatory HCC. Conclusion: Our findings reveal the mechanisms of mTORC1-driven noninflammatory HCC and provide insight into further development of a protective strategy against noninflammatory HCC.